Assessment of Behavioral and Palynological Attributes of Apis mellifera L. Foragers in a Mustard Ecosystem - Riju Nath; Samrat Saha; Nripendra Laskar (Sociobiology)
An investigation was carried out to assess different foraging activities of Apis mellifera L. in the mustard ecosystem by placing six strong A. mellifera colonies along the borders of mustard fields in the Terai agroecological region of West Bengal during 2019 and 2020. During this period, foragers of A. mellifera had a foraging duration of 9.41 ± 0.33 hours/day. Their activity was higher during mid-day than in the early morning and late evening hours. Temperature and bright sunshine hours strongly correlate with foraging duration and intensity. On the other hand, relative humidity and rainfall were negatively correlated with bee foraging. Foragers were found to spend maximum time on each flower at 11:00 – 13:00 hours, and their abundance was also high during this time interval. At initial hours of observation, i.e., at 07:00 – 09:00, foraging was minimal. The palynological assessment suggested that the foragers carry about 568,640 ± 15426.52 pollen on their bodies during peak foraging time. Apart from the pollen of Brassica sp., some other pollen types belonging to Ageratum conyzoides, Amaranthus/Chenopodium sp., Cajanus cajan, Leucas aspera, Spilanthes sp., and species of Polygonaceae and Solanaceae were also recovered from pollen load. However, these non-Brassica pollen frequency was very low in the pollen spectrum. This study provides information to assist local beekeepers in effectively managing their colonies by correlating foraging activity with weather parameters, and it will also advise mustard growers on establishing a prudent pesticide application schedule that will protect foraging bees from pesticide exposure.